2023
DOI: 10.1039/d2cs00191h
|View full text |Cite
|
Sign up to set email alerts
|

Single-atom catalysts: promotors of highly sensitive and selective sensors

Abstract: This review summarizes the sensing mechanism, design strategies, structural and performance advantages of single-atom catalysts and their sensing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 284 publications
(350 reference statements)
0
5
0
Order By: Relevance
“…17,18 Early research showed that compared to traditional gas sensing materials, SACs could maintain high sensitivity and rapid response even at low temperatures. 19–22 The efficient catalytic activity of metal single atoms and their synergistic effects with metal supports play crucial roles in this context. 23–25 Over the past decades, various strategies have been employed to control emissions of contaminated gases, including absorption, condensation, biological degradation, and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Early research showed that compared to traditional gas sensing materials, SACs could maintain high sensitivity and rapid response even at low temperatures. 19–22 The efficient catalytic activity of metal single atoms and their synergistic effects with metal supports play crucial roles in this context. 23–25 Over the past decades, various strategies have been employed to control emissions of contaminated gases, including absorption, condensation, biological degradation, and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based single-atom catalysts (SACs) have aroused increasing interest in the fields of wastewater treatment and environmental remediation in the past few years due to their merits of exceptional atomic utilization, high selectivity, and structural stability. In addition, SACs can be used to establish ideal catalytic systems to investigate the interactions between the reactant molecules and the active sites of isolated metal atoms on catalyst surfaces. It has been widely reported that such catalysts could exhibit excellent removal performance of aqueous pollutants through modulating the catalytic reaction pathways in the Fenton-like systems, e.g., radical and nonradical pathways. The remarkable catalytic performance of the carbon-based SACs in Fenton-like reactions can also inspire their extended application in other AOP systems.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Compared with other techniques for target quantification, such as UV-vis, LC-MS, ELISA and luminescence methods, electrochemical methods have the characteristics of fast response, miniaturizable and high sensitivity. [14][15][16] As far as the development of SACs based electrocatalytic sensors are concerned, the following points are still worth further discussion: (1) structure-performance relationships between the structure of SACs and the electrochemical sensing, (2) selectivity in the face of the inherent catalytic activity of SACs, and (3) structural regulation methods for SACs according to different substrates and electrochemical systems.…”
Section: Introductionmentioning
confidence: 99%